Academic burnout pada mahasiswa Merdeka Belajar Kampus Merdeka (MBKM): Bagaimana peranan efikasi diri? - Mutiara Pamungkas Wibowo; Suroso; Isrida Yul Arifiana (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between self-efficacy and academic burnout in students who run the Merdeka Learning Campus Merdeka (MBKM) program. The hypothesis put forward is a negative relationship between self-efficacy and academic burnout. The research design uses a correlational quantitative research method. This research was conducted with 124 students from the University of 17 August 1945 Surabaya as participants. The instruments used in this study are the academic burnout scale according to Maslach's theory (2003) and the self-efficacy scale according to Bandura's theory (1997). Sampling in this study uses an accidental sampling technique. The data analysis technique in this study uses the product moment test. Based on the results of the data analysis that has been done, it is found that there is a negative and significant relationship between self-efficacy and academic burnout. Acceptance of the hypothesis in this study shows that self-efficacy is strongly related to academic burnout in students who carry out the Independent Learning Campus Merdeka (MBKM) program. Keywords: Self-Efficacy, Academic Burnout, Students, Independent Learning Campus Merdeka (MBKM)